Avaliação do estresse oxidativo em músculos soleus e extensor longo dos dedos de ratos submetidos a dieta hipoproteica e hiperglicídica logo após o desmame - Silva, Flavia Hosaki Silvino da (2017)
The aim of this study was to evaluate the oxidative stress and antioxidant defense in soleus and extensor digitorum longus (EDL) muscles of growing rats fed a low-protein, high-carbohydrate (LPHC; 6% protein, 74% carbohydrate) diet for 15 days. The LPHC diet increased the total antioxidant capacity in the soleus muscles by 50%. There was an increase in the carbonylated proteins with no increase in malonaldehyde content. Despite the 22% increase in xanthine oxidase activity, the activity of the antioxidant enzymes also increased significantly. The LPHC diet increased the malonaldehyde levels in EDL muscles by 80% in addition to a 66% increase in XO activity with no alterations in antioxidant enzyme activity except for glutathione peroxidase. The GSH/GSSG ratio was lower in both muscles. These results suggest that the soleus muscle responds better to increasing ROS production.